Air quality monitoring and remote control system using Arduino IDE - Teh, Siang Wen (Nanyang Technological University, 2021)
Smart Home Automation (SHA), focusing on the automation of household appliances by implementing Internet of Things (IoT) has been on the rise. With IoT implemented, parameters of interest captured by sensors can be sent to the Internet cloud to display for the users or in-depth analysis. Furthermore, IoT allows users to control their devices that are connected to the Internet through the IoT Platform. One area in which SHA can be integrated is home cooling. With IoT technology, home cooling can be self-regulated through pre-defined algorithms or manual control, saving household expenses. To further reduce household expenses, roof ventilation has become more prevalent in replacing air conditioning. This project aims to design an Air Monitoring and Control System by using IoT to display the Temperature, Humidity, and Wind Speed through an online dashboard and to create an automated control system. The ESP32 with an integrated WiFi module is the best microcontroller for IoT implementations. This system consists of Master and Slave Devices, each being controlled by an ESP32 and Arduino UNO respectively. The Slave Device mainly measured the wind speed while the Master Device measured the temperature and humidity while transmitting all the data collected. The devices are communicated through Radio Frequency (RF). An automated control system is being implemented to improve the battery life as the WiFi module need not be in operation all the time waiting for the signal being sent by the users.